Evaluating loss-aware update mechanisms for distributed virtual environments - Loo, Yan Long. (2013)
Distributed virtual environment (DVE) enables multiple users from different regions of the world connecting together to interact and communicate with each other in a common virtual environment. Due to recent trends of raising popularity of massively multiplayer